Investigation of Thermal Behavior for Natural Fibres Reinforced Epoxy using Thermogravimetric and Differential Scanning Calorimetric Analysis - F. A., Fauzi; Z., Ghazalli; Siregar, J. P.; Tezara, C. (EDP Sciences, 2016)
This paper presented the research works on the investigation of the thermal behavior of the natural fibres; i.e. pineapple leaf fibre, kenaf fibre and mengkuang fibres reinforced epoxy. The thermogravimetric analysis and differential scanning calorimetric analysis were used to measure the thermal behavior of the treated and untreated pineapple, kenaf and mengkuang fibres reinforced epoxy. The samples for both analysis were subjected to maximum temperature 600°C at the heating rate of 10°C/min. The results showed that the treated fibres show higher maximum peak temperature as compared to the untreated fibres. Additionally, the glass transition temperature showed a lower value for all treated fibre. It can be concluded that investigation of thermal properties of these natural fibres could improve the utilization of natural fibre composites in various applications i.e. sports applications.